Agro techniques for growth promotion and increasing bark yield in Ashoka (Saraca asoca Roxb.) - Jinsy V S (Department of Agronomy, College of Agriculture, 2010)
Ashoka is an important medicinal tree gaining economic significance in recent years. As the domestic production of the officinal parts of ashoka is quite insufficient to meet the demand of ayurvedic medicine manufacturing units there is an urgent need for developing appropriate technologies for growth promotion and increasing bark yield in ashoka. Three separate experiments were carried out at the Instructional Farm attached to the College of Agriculture, Vellayani to develop agro techniques for growth promotion and increasing bark yield in ashoka during 2009-10. The nursery trial on ‘Techniques for quality planting material production’ consisting of combinations of four root trainer techniques, viz, root trainer (individual tubes – R1), root trainer (blocks – R2), poly bags (R3) and mud pots (R4) and four rooting media, viz, potting mixture (M1), potting mixture +dual inoculation with Rhizobium and AMF (M2), potting mixture + dual inoculation with Rhizobium and AMF + Rock powder (M3) and potting mixture +dual inoculation with Rhizobium and AMF + Rock powder + mixture of vermicompost, FYM and composted coir pith (M4) was conducted in CRD with four replications. The field experiment on ‘Micro site enrichment techniques for growth promotion’ consisting of combinations of four in situ rain water harvests, viz, micro site enrichment, micro site enrichment + micro catchments, micro site enrichment + micro catchments + vertical mulching and POP recommendations and two levels of irrigation, viz, irrigation at 50 % depletion of moisture and life saving irrigation was carried out in FRBD with three replications. The third trial on ‘Techniques for increasing bark yield’ comprising four treatments, viz, NAA 50 mg l-1, Kinetin 50 mg l-1 , Combination of NAA 50 mg l-1 and Kinetin 50 mg l-1 and control was conducted in CRD with three replications. In the nursery trial, dual inoculation of seeds with Rhizobium and AMF and sowing in mud pots containing enriched rooting media consisting of potting mixture, rock powder and mixture of vermicompost, FYM and composted coir pith was found beneficial for improving biomass accumulation in ashoka seedlings. The quality of the planting stock was evaluated based on three growth indices, viz, sturdiness quotient (SQ), root growth potential (RGP) and seedling growth potential (SGP). Among the different treatment combinations, higher values of SQ were shown by R2M3 followed by R1M4. Mud pots filled with rooting medium consisting of a consortium of bioinoculants and biomanures sprinkled with rock powder registered higher root growth and seedling growth potential. Besides, economic analysis of the system also proved its contribution in relation to gross income, net income and BCR.